Effects of the upward-increasing gradient magnetic field on soot properties in ethylene inverse diffusion flames with different oxygen concentrations - Ying, Yaoyao; Duan, Jiaqi; Liu, Dong (Frontiers in Energy Research, 2022)
The effects of the upward-increasing gradient magnetic field on soot properties are experimentally investigated in ethylene inverse diffusion flames with different oxygen concentrations. The soot morphology, nanostructure, graphitization degree, and oxidation reactivity are obtained by high-resolution transmission electron spectroscopy (HRTEM), X-ray diffractometer (XRD), and thermogravimetric analyzer (TGA), respectively. The upward-increasing gradient magnetic field is induced by two Nd-Fe-B permanent magnets with different thicknesses. The results show that the magnetic field influences the soot properties mainly by affecting the distributions of paramagnetic O2 and OH radicals in the flames. The soot samples are more graphitized in the flame with higher O2 concentration, which contains a longer fringe length and smaller fringe tortuosity. Fullerene-like structures are more apparent with increasing oxygen content. The soot fringe length decreases and fringe tortuosity increases when the upward-increasing gradient magnetic field is applied. The application of the magnetic field enhances the soot oxidation reactivity, and it shows the greatest effect on the oxidation reactivity of soot produced in the flame with 21% O2 content.